Perbedaan Efektifitas Metode Demonstrasi Dengan Pemutaran Video Tentang Pemberantasan DBD Terhadap Peningkatan Pengetahuan Dan Sikap Anak SD Di Kecamatan Wedarijaksa Kabupaten Pati - Cahya Wibawa (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background : This researches aim to compare difference of effectiveness between demonstration method and video twiddling method on DHF prevention in iencreasing knowledge and attitude of Elementary School student in District of Wedarijaksa, Sub-Province Pati.Method : This research type was Quasi Experiment with Non equivalent control group design. Research sampel were 60 students. Sampling technique was simple allocation assignment random. Sampel for demonstration method were 30 students from SD Negeri Pagerharjo,and sampel for video twidding method were 30 students from SD Negeri Tluwuk. Data analysis method was two paired test.Result : Research results indicated proven that there are differences between demonstration method and video twiddling method in improving knowledge of DHF pandemic of Elementary school students, that is shown increasing of knowledge 58,97% higher at group treatment of demonstration compared with video twiddling treatment which is increasing on 24,19%. Proven that there are significant differences between demonstration method and video twiddling method in improving DHF pandemic attitude of Elementary school students,which is shown by Elementary school students attitude of DHF pandemic at demonstration method group is higher than Elementary schoolchild attitude of DHF pandemic at video twiddling method group, (29,68% compared to 19,71%). The research result indicated there were differences of retention between knowledge of demonstration method group and video twiddling method group, which was shown by smaller knowledge retention at group treatment of demonstration compared to group treatment of video twiddling, (4,25% compared to 7,05%). The research result also shown that there were differences of retention between attitude of demonstrate method group and video twiddling method group, that is shown by smaller attitude retention at group treatment of demonstration compared to group treatment of video twiddling, (4,42% compared to 8,63%).The conclusion of this research are demonstration is more effective than video twiddling to increase child attitude and knowledge of Elementary School in DistrictOf Wedarijaksa, Sub-Province Pati about preventing of DHF.Keywords: Effectiveness, Knowledge, Attitude, DHF, Demonstration, Video Twiddling